BUILDING COMPETITIVE ADVANTAGE THROUGH ABSORBTIVE CAPACITY AND OPEN INNOVATION IN INDONESIA SME’S.CASE STUDY IN BALIKPAPAN, INDONESIA - Wang, Nathan; Benny Aristo (DeReMa (Development Research of Management): Jurnal Manajemen, 2025)
Small and Medium Enterprises (SMEs) are vital contributors to Indonesia’s economy, particularly in the culinary sector, which faces intense competition and rapidly shifting consumer demands. This study investigates the effects of innovation strategy, absorptive capacity, and open innovation (inbound and outbound) on the performance of culinary SMEs in Balikpapan, East Kalimantan. An explanatory quantitative design was employed, with data collected through structured questionnaires distributed to 180 SMEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The measurement model confirmed construct validity and reliability, with all outer loadings, Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted (AVE) exceeding recommended thresholds. Results of the structural model indicate that absorptive capacity has a significant positive influence on innovation strategy as well as on inbound and outbound open innovation. Innovation strategy positively affects inbound open innovation, but its relationship with outbound open innovation was not supported. Both inbound and outbound open innovation significantly enhance SME performance, with inbound open innovation showing the stronger effect. The model demonstrated moderate to substantial explanatory power (R² = 0.446–0.757) and good predictive relevance (Q²), particularly for inbound open innovation and SME performance. These findings emphasize the importance of absorptive capacity as the foundation for innovation and competitiveness, while inbound open innovation emerges as the key driver of performance improvement. The study contributes to the SME innovation literature by integrating absorptive capacity, innovation strategy, and open innovation in an emerging economy context, while also offering practical guidance for SME managers and policymakers to strengthen innovation capabilities and foster sustainable growth. Abstrak dalam Bahasa Indonesia : Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan kontributor penting bagi perekonomian Indonesia, khususnya di sektor kuliner yang menghadapi persaingan ketat serta perubahan permintaan konsumen yang cepat. Penelitian ini meneliti pengaruh strategi inovasi, kapasitas serap, dan inovasi terbuka (inbound dan outbound) terhadap kinerja UMKM kuliner di Balikpapan, Kalimantan Timur. Desain penelitian yang digunakan adalah kuantitatif eksplanatori, dengan pengumpulan data melalui kuesioner terstruktur yang dibagikan kepada 180 UMKM dan dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) pada SmartPLS 4. Model pengukuran mengonfirmasi validitas dan reliabilitas konstruk, dengan seluruh outer loading, Cronbach’s Alpha, Composite Reliability, dan Average Variance Extracted (AVE) melampaui ambang batas yang direkomendasikan. Hasil model struktural menunjukkan bahwa kapasitas serap berpengaruh positif signifikan terhadap strategi inovasi serta inovasi terbuka inbound dan outbound. Strategi inovasi berpengaruh positif terhadap inovasi terbuka inbound, tetapi hubungannya dengan inovasi terbuka outbound tidak didukung. Baik inovasi terbuka inbound maupun outbound terbukti meningkatkan kinerja UMKM secara signifikan, dengan inovasi terbuka inbound menunjukkan pengaruh yang lebih kuat. Model penelitian menunjukkan daya jelaskan yang moderat hingga substansial (R² = 0,446–0,757) serta relevansi prediktif (Q²) yang baik, khususnya untuk inovasi terbuka inbound dan kinerja UMKM. Temuan ini menekankan pentingnya kapasitas serap sebagai fondasi inovasi dan daya saing, sementara inovasi terbuka inbound muncul sebagai penggerak utama peningkatan kinerja. Penelitian ini berkontribusi pada literatur inovasi UMKM dengan mengintegrasikan kapasitas serap, strategi inovasi, dan inovasi terbuka dalam konteks ekonomi berkembang, serta memberikan panduan praktis bagi manajer UMKM dan pembuat kebijakan untuk memperkuat kapabilitas inovasi dan mendorong pertumbuhan berkelanjutan.